Uma história que não tem fim: um estudo sobre a fantasia literária - Marques, Mirane Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work proposes a revision and delimitation of the fantasy genre that will fundamentally occur through the dialogue with the notions of fairy tales and fantasy as formulated by J. R. R. Tolkien (2013) in his essay On Fairy Stories. In terms of revision, it will be done a comparison between The Lord of the Rings author's theory and the ones by critics such as Manlove (1982, 1990), Laetz and Johnston (2008), Stableford (1990), Attebery (1980, 1990, 1992). Regarding delimitation, it will interest us, particularly, the counterpoint with the marvelous as thought by Todorov (2007). This posture will contribute to fantasy's affirmation as a better lineate and coherent genre, contributing also to the cohesion of the marvelous itself, since it is a broad genre that brings together several heterogeneous works. Thus fantasy will appear as one of marvelous' limits, precisely when the narrative's supernatural elements have what Tolkien calls internal consistency of reality, constituting a Secondary World. Therefore, while in the marvelous it is found an integration (and harmonization) between natural and supernatural, fantasy imply a disjunction between two realities, two worlds. According to this conception, this work proposes a reading of Micahel Ende's The Neverending Story focusing, on the one hand, in the narrative procedures that favor the fantasy construction, and, on the other hand, in the metalinguistic aspect that occupies a central position in the German writer's novel. Therefore, the approach of Ende's work must simultaneously allow the contact between fantasy's theory and literary work as well as foment connections with other narratives with similar procedures (such as The Chronicles of Narnia, The Lord of the Rings, The Silmarillion, Farmer Giles of Ham and the Harry Potter series), consequently contributing to a better definition of the fantasy genre itself

Este trabalho propõe uma revisão e uma delimitação do gênero fantasia que se dará fundamentalmente por meio do diálogo com as noções de contos de fadas e de fantasia tal como formuladas por J. R. R. Tolkien (2013) em seu ensaio Sobre contos de fadas. Em termos de revisão, procuraremos o cotejo entre a teoria do autor de O senhor dos anéis e críticos tais como Manlove (1982, 1990), Laetz e Johnston (2008), Stableford (1990), Attebery (1980, 1990, 1992). No que tange à delimitação, interessar-nos-á particularmente o contraponto com a concepção do gênero maravilhoso proposta por Todorov (2007). Tal postura contribuirá para a afirmação da fantasia como um gênero mais bem delineado e coerente, contribuindo, também, para a coesão do próprio maravilhoso, gênero demasiado amplo que congrega obras muito heterogêneas. A fantasia surgirá, desse modo, como um dos limites do maravilhoso, justamente quando os elementos sobrenaturais da narrativa possuem o que Tolkien chama de consistência interna de realidade, constituindo um Mundo Secundário. Portanto, enquanto no maravilhoso encontra-se uma integração (e harmonização) entre o natural e o sobrenatural, a fantasia implicará uma disjunção entre duas realidades, dois Mundos. Segundo essa concepção, propomos uma leitura de A história sem fim, de Michael Ende, focada, por um lado, nos procedimentos narrativos que favorecem a construção da fantasia, e, por outro, no aspecto metalinguístico que ocupa uma posição central no romance do escritor alemão. A abordagem da obra de Ende, dessa forma, deverá simultaneamente permitir o contato entre a teoria sobre a fantasia e a obra literária e favorecer conexões com outras narrativas (como As crônicas de Nárnia, O senhor dos anéis, O silmarillion, Mestre Gil de Ham e a série Harry Potter) que dela se aproximam, contribuindo, consequentemente, para uma melhor delimitação do...
Keywords: Literatura fantástica; Fantasia na literatura; O maravilhoso na literatura; Tolkien, J. R. R